MANAJEMEN PEMELIHARAAN TERNAK BABI PADA PETERNAKAN BABI TOLU WEI SUMBA TIMUR - Datta, Frans Umbu; Foeh, Nancy Diana Frederika Katerina; Detha, Annytha Ina Rohi; Mandala, Graziela Angelicha; Bero, Catharina De Ricci Inye; Toha, Larry Richard Wellem; Ndaong, Nemay Anggadewi (Jurnal Media Tropika, 2024)
Tolu Wei Pig Farm has a population of 444 pigs, including 14 heifers, 26 pregnant pigs, 15 parturient pigs, 153 newborn piglets, 98 weaned piglets, 5 studs, and 133 fattening pigs of various types. The pigs kept are Landrace, Duroc, and Yorkshire. This Field Work Practice (PKL) activity aims to find out and analyze housing management, the type of feed given at each growth period, mating management, health management at various breeding phases, and the implementation of waste processing at the Tolu Wei Pig Farm. The methods used are observation, interviews, practice, and education. Based on this method, it is known that the housing system implemented by the Tolu Wei Pig Farm is intensive, feeding is carried out twice a day, namely in the morning and evening with the type of feed given in the form of a mixture of pellets and pigmix, there is application of biosecurity and sanitation and treatment is carried out on sick livestock. , reproductive management is carried out by means of natural mating and artificial insemination (AI), and processing of livestock waste is carried out by collecting it in a special area for waste and pig feces by drying in the sun. The conclusion obtained is that the housing management has met good housing standards, the feed management implemented can meet nutritional needs, the health management in the form of biosecurity implemented is good, and the reproductive management implemented has met good standards.